High-temperature-resistant binder and preparation method thereof

By designing a polyimide resin containing siloxane and imide unit main chains, and introducing epoxy side groups and tannic acid, the problems of insufficient high-temperature curing and substrate adaptability of existing high-temperature adhesives are solved, achieving room temperature curing and strong adhesion at high temperatures, making it suitable for a variety of substrates.

CN120923781APending Publication Date: 2025-11-11COMO (SHANGHAI) NEW MATERIAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202511191344.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-25
Publication Date
2025-11-11

Smart Images

  • Figure CN120923781A_ABST
    Figure CN120923781A_ABST
Patent Text Reader

Abstract

The invention relates to a high-temperature-resistant polymer binder and a preparation method thereof. The binder is composed of a mixture of resin containing a siloxane unit polyimide main chain and an epoxy group side chain and tannic acid. Wherein the main chain containing siloxane and imide units endows the adhesive with excellent heat-resistant stability, excellent processability and excellent adhesion with glass and ceramic materials, and the adhesive can be cured at room temperature through the epoxy side group; the mixed tannic acid can form strong interface bonding with a polymer film and a metal material through a multiple hydrogen bond network, so that the tannic acid has important application prospects in the fields of semiconductor packaging, thermal interface materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of adhesive technology, and specifically relates to a polyimide resin and its preparation method, as well as the corresponding composition, preparation method and use as a high-temperature resistant adhesive. Background Technology

[0002] High-temperature resistant polymer adhesives are a class of polymeric materials capable of maintaining stable bonding performance in environments above 200°C for extended periods. Their development is inextricably linked to advancements in high-tech fields such as aerospace and energy. Looking back, in the 1950s, with the rise of jet engines and rocket technology, traditional adhesives could no longer meet the requirements of use in extreme thermal environments, directly spurring the development of the first generation of high-temperature resistant polymer adhesives. Early phenolic resins and modified epoxy resins, while capable of short-term operation at 200-250°C, suffered from significant drawbacks such as high brittleness and poor resistance to heat and oxygen aging. In the 1960s and 70s, the emergence of aromatic heterocyclic polymers such as aromatic polyimide (PI) and polybenzimidazole (PBI) raised the upper temperature limit of polymer adhesives to 300-400°C, meeting the needs of spacecraft thermal protection systems at the time. However, the rapid development of technologies such as semiconductor packaging and flexible thermal interface materials in recent years has placed more stringent demands on high-temperature resistant polymer adhesives. Besides meeting the requirements for long-term high-temperature service, these adhesives also need to possess excellent processing and curing properties, as well as good adaptability to different substrates (metals, ceramics, films, peel materials, etc.). For example, Chinese invention patent (CN 201810457995.2) discloses a method to improve the high-temperature adhesion of polyimide-based adhesives by introducing acetylene-based phenyl groups and Si-O-Si units at the molecular chain end. However, this type of adhesive requires high-temperature heat treatment at 350-400℃ for 1-6 hours to complete the high-temperature curing reaction. Chinese invention patent (CN 202210117854.2) discloses a method for synthesizing high-temperature resistant polyimide structural adhesives by introducing phenylacetylene groups and esterification reaction, but this type of structural adhesive still requires curing at close to 380℃ and a pressure of 0.5-15 MPa.

[0003] Therefore, the key to expanding the application of such materials and meeting the increasingly demanding needs of different fields is to develop novel adhesives that combine good processing performance, excellent high-temperature adhesion, and adaptability to various substrate surfaces through macromolecular structure design and multiple action mechanisms. Summary of the Invention

[0004] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to provide a high-temperature resistant polymer adhesive that can be cured at room temperature, has excellent high-temperature bonding strength, and can be used on a variety of substrates.

[0005] This invention provides a high-temperature resistant polymer adhesive and its preparation method, comprising a mixture of a polyimide backbone containing siloxane units and an epoxy group side chain, and tannic acid. The siloxane and imide backbone endows this type of adhesive with excellent heat resistance, hydrophobicity, and excellent adhesion to glass and ceramic materials, while the epoxy side groups enable the adhesive to cure at room temperature. The incorporated tannic acid forms strong interfacial bonds with polymer films and metal materials through a multi-hydrogen bond network.

[0006] In a first aspect, a polyimide resin has a main chain comprising repeating imide rings and siloxane segments, and a side chain comprising epoxy groups; The molar fraction of siloxane unit segments in the polymer resin backbone is (10-50) mol%. The molar fraction of epoxy side group segments is (30-50) mol%.

[0007] Secondly, the above-mentioned method for preparing polyimide resin involves a condensation reaction of dianhydride monomer, diamine monomer containing carboxyl or hydroxyl groups, and diamine siloxane to obtain a siloxane-block polyimide resin, followed by the addition of epichlorohydrin to perform a grafting reaction with the hydroxyl or carboxyl groups in the resin to obtain an epoxidized polyimide resin. The dianhydride monomer is selected from one or more combinations of 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA), 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA), hexafluoro dianhydride (6FDA), and bisphenol A type diether dianhydride (BPADA). The diamine monomer containing a carboxyl or hydroxyl group is selected from one or more combinations of 3,5'-diaminobenzoic acid, 4,4'-diaminobiphenyl-2,2'-dicarboxylic acid, 9,9-bis(3-amino-4-hydroxyphenyl)fluorene, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane or 3,3'-dihydroxybenzidine; The diaminosiloxane is selected from one or more combinations of 1,3-bis((aminopropyl)tetramethyldisiloxane) and diaminopropylpolydimethylsiloxane.

[0008] Preferably, the dianhydride monomer, the diamine monomer containing a carboxyl or hydroxyl group, and the diamine siloxane are copolymerized in a one-step solution process at high temperature.

[0009] Furthermore, the preparation method specifically includes: S1. Under gas protection, the dianhydride monomer is dissolved in an organic solvent; S2. Under gas protection, diamines containing siloxane units and diamine monomers containing carboxyl or hydroxyl groups are gradually added to the dianhydride solution. After all the diamine monomers are dissolved, the mixture is stirred at room temperature for (18-24) h to obtain a polymer solution. S3. Add a catalyst to the polymer solution and heat the reaction solution to (100-120)℃. React at this temperature for (10-12)h. Further heat the reaction system to (190-200)℃ and react at this temperature for (12-24)h to finally obtain a viscous polyimide solution. S4. Add sodium hydroxide to the above-mentioned synthetic solution, add epichlorohydrin dropwise, and react at 90-100℃ for 2 hours.

[0010] Preferably, the organic solvent in step S1 is selected from any one or a combination of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and N-methylpyrrolidone (NMP).

[0011] Preferably, the gas mentioned in steps S1 and S2 is an inert gas or nitrogen.

[0012] Preferably, the total mass fraction of the solid reactants in step S2 is (15-25) wt%.

[0013] Preferably, in step S3, the molar ratio of the diamine containing a siloxane unit to the diamine containing a carboxyl or hydroxyl group is 1 / 9 to 5 / 5.

[0014] Preferably, the catalyst in step S3 is selected from pyridine or isoquinoline.

[0015] Preferably, in step S4, the amount of sodium hydroxide used is (0.1-0.2) wt% of the mass of epichlorohydrin.

[0016] Thirdly, a composition comprising: the polyimide resin described above and tannic acid.

[0017] Preferably, the mass of tannic acid in the composition is (10-20) wt% of the mass of the polyimide resin.

[0018] Fourthly, the method for preparing the above-described composition includes: adding tannic acid to a polyimide resin solution for physical blending; Preferably, tannic acid is added to the polyimide resin solution for physical blending under inert gas or nitrogen protection. Preferably, tannic acid is added to the polyimide resin solution and blended for 12-48 hours; Preferably, tannic acid is added to the polyimide resin solution for blending, and then the mixture is degassed.

[0019] Fifthly, the above-described composition is used as a high-temperature resistant adhesive.

[0020] Furthermore, when the composition is applied to the bonding of copper plates or polymer films, the bonding strength retention rate is ≥80% after heat treatment at 200°C for 10 hours.

[0021] Sixthly, the use of the above-described compositions for bonding at the interface of the same or different materials, wherein the materials include: polymer film materials, metallic materials or inorganic non-metallic materials.

[0022] The beneficial effects achieved by this invention are as follows: (1) This invention endows such adhesives with excellent thermal stability, hydrophobicity and excellent adhesion to inorganic non-metallic materials such as glass and ceramics by designing a main chain containing siloxane and imide units.

[0023] (2) In this invention, the epoxy side group is introduced so that the adhesive can be cured at room temperature, and the mixed tannic acid can form a strong interfacial bond with the polymer film and metal material through a multi-hydrogen bond network, and can still maintain a good bonding effect at high temperature. Attached Figure Description

[0024] Figure 1 Photograph of the high-temperature resistant adhesive prepared in Example 1. Detailed Implementation

[0025] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0026] The aforementioned dianhydride and diamine monomers were purchased from Tianjin Zhongtai Materials Technology Co., Ltd., the diamine siloxane was purchased from Guangzhou Yuanda New Materials Co., Ltd., and the other raw materials were purchased from Sinopharm Group.

[0027] Example 1 Under nitrogen protection, benzophenone tetracarboxylic dianhydride (BTDA) monomer was dissolved in dimethylacetamide (DMAc) solvent. After complete dissolution, equimolar amounts of 1,3-bis(aminopropyl)tetramethyldisiloxane and 3,5'-diaminobenzoic acid were added to the dianhydride solution, wherein the molar fraction of 1,3-bis(aminopropyl)tetramethyldisiloxane in the diamine was 30 mol%, the mass fraction of the reactants was controlled at 20 wt%, and the mass fraction of the solvent was 80 wt%. The mixture was stirred at room temperature for 18 h. Then, 0.5 wt% (relative to the total amount of reactants) of isoquinoline was added dropwise to the reaction system, the temperature of the reaction solution was raised to 120 °C, and the reaction was carried out for 10 h. The reaction temperature was further increased to 190 °C, and the reaction was carried out for 24 h to obtain a viscous polyimide reaction solution. After cooling to room temperature, 0.1 wt% NaOH and epichlorohydrin were added to the reaction system, wherein the molar fraction of epichlorohydrin was 30 mol% of the polyimide backbone. The reaction was carried out at 90 °C for 2 h. After cooling to room temperature, tannic acid was added to the system at a mass fraction of 10 wt% (relative to the total amount of polyimide resin), and the mixture was stirred evenly. The synthesized adhesive was used to adhere polyimide films, copper sheets, and glass plates. The solvent was removed at 80 °C, and then the mixture was cured at room temperature for 5 h.

[0028] Example 2 Under nitrogen protection, BTDA monomer was dissolved in DMAc solvent. After complete dissolution, equimolar amounts of diaminopropyl polydimethylsiloxane and 3,3'-dihydroxybenzidine were added to the dianhydride solution, wherein the molar fraction of 1,3-bis(aminopropyl)tetramethyldisiloxane in the diamine was 30 mol%, the mass fraction of the reactants was controlled at 20 wt%, and the mass fraction of the solvent was 80 wt%. The mixture was stirred at room temperature for 18 h. Then, 0.5 wt% isoquinoline (relative to the total amount of reactants) was added dropwise to the reaction system, the temperature of the reaction solution was raised to 120 °C, and the reaction was carried out for 10 h. The reaction temperature was further increased to 190 °C, and the reaction was carried out for 24 h to obtain a viscous polyimide reaction solution. After cooling to room temperature, 0.1 wt% NaOH and epichlorohydrin were added to the reaction system, wherein the molar fraction of epichlorohydrin was 30 mol% of the polyimide backbone, and the reaction was carried out at 90 °C for 2 h. After cooling to room temperature, tannic acid was added to the system at a mass fraction of 10 wt% (relative to the total amount of polyimide resin), and the mixture was stirred evenly. The synthesized adhesive was used to adhere polyimide films, copper sheets, and glass plates. The solvent was removed at 80 °C, and then the mixture was cured at room temperature for 5 h.

[0029] Example 3 Under nitrogen protection, ODPA monomer was dissolved in DMAc solvent. After complete dissolution, equimolar amounts of 1,3-bis(aminopropyl)tetramethyldisiloxane and 3,5'-diaminobenzoic acid were added to the dianhydride solution, wherein the molar fraction of 1,3-bis(aminopropyl)tetramethyldisiloxane in the diamine was 30 mol%, the mass fraction of the reactants was controlled at 20 wt%, and the mass fraction of the solvent was 80 wt%. The mixture was stirred at room temperature for 18 h. Then, 0.5 wt% isoquinoline (relative to the total amount of reactants) was added dropwise to the reaction system, the temperature of the reaction solution was raised to 120 °C, and the reaction was carried out for 10 h. The reaction temperature was further increased to 190 °C, and the reaction was carried out for 24 h to obtain a viscous polyimide reaction solution. After cooling to room temperature, 0.1 wt% NaOH and epichlorohydrin were added to the reaction system, wherein the molar fraction of epichlorohydrin was 50 mol% of the polyimide backbone, and the reaction was carried out at 90 °C for 2 h. After cooling to room temperature, tannic acid was added to the system at a mass fraction of 10 wt% (relative to the total amount of polyimide resin), and the mixture was stirred evenly. The synthesized adhesive was used to adhere polyimide films, copper sheets, and glass plates. The solvent was removed at 80 °C, and then the mixture was cured at room temperature for 5 h.

[0030] Example 4 Under nitrogen protection, BTDA monomer was dissolved in DMAc solvent. After complete dissolution, equimolar amounts of 1,3-bis(aminopropyl)tetramethyldisiloxane and 3,5'-diaminobenzoic acid were added to the dianhydride solution, wherein the molar fraction of 1,3-bis((aminopropyl)tetramethyldisiloxane) in the diamine was 30 mol%, the reactant mass fraction was controlled at 20 wt%, and the solvent mass fraction was 80 wt%. The mixture was stirred at room temperature for 18 h. Then, 0.5 wt% isoquinoline (relative to the total reactant amount) was added dropwise to the reaction system, and the reaction temperature was raised to 120 °C. After 10 hours, the reaction temperature was further increased to 190℃, and the reaction was continued for 24 hours to obtain a viscous polyimide reaction solution. After cooling to room temperature, 0.1 wt% NaOH and epichlorohydrin were added to the reaction system, wherein the molar fraction of epichlorohydrin was 30 mol% of the polyimide backbone. The reaction was carried out at 90℃ for 2 hours. After cooling to room temperature, tannic acid was added to the system at a mass fraction of 20 wt% (relative to the total amount of polyimide resin), and the mixture was stirred uniformly. The synthesized adhesive was used to adhere polyimide films, copper sheets, and glass plates. The solvent was removed at 80℃, and then cured at room temperature for 5 hours.

[0031] Example 5 Under nitrogen protection, BTDA monomer was dissolved in DMAc solvent. After complete dissolution, equimolar amounts of 1,3-bis(aminopropyl)tetramethyldisiloxane and 3,5'-diaminobenzoic acid were added to the dianhydride solution, wherein the molar fraction of 1,3-bis((aminopropyl)tetramethyldisiloxane) in the diamine was 50 mol%, the reactant mass fraction was controlled at 20 wt%, and the solvent mass fraction was 80 wt%. The mixture was stirred at room temperature for 18 h. Then, 0.5 wt% isoquinoline (relative to the total reactant amount) was added dropwise to the reaction system, and the reaction temperature was raised to 120 °C. After 10 hours, the reaction temperature was further increased to 190℃, and the reaction was continued for 24 hours to obtain a viscous polyimide reaction solution. After cooling to room temperature, 0.1 wt% NaOH and epichlorohydrin were added to the reaction system, wherein the molar fraction of epichlorohydrin was 30 mol% of the polyimide backbone. The reaction was carried out at 90℃ for 2 hours. After cooling to room temperature, tannic acid was added to the system at a mass fraction of 20 wt% (relative to the total amount of polyimide resin), and the mixture was stirred uniformly. The synthesized adhesive was used to adhere polyimide films, copper sheets, and glass plates. The solvent was removed at 80℃, and then cured at room temperature for 5 hours.

[0032] Comparative Example 1 Under nitrogen protection, BTDA monomer was dissolved in DMAc solvent. After complete dissolution, equimolar amounts of 1,3-bis(aminopropyl)tetramethyldisiloxane and 3,5'-diaminobenzoic acid were added to the dianhydride solution, wherein the molar fraction of 1,3-bis(aminopropyl)tetramethyldisiloxane in the diamine was 30 mol%, the reactant mass fraction was controlled at 20 wt%, and the solvent mass fraction was 80 wt%. The mixture was stirred at room temperature for 18 h. Then, 0.5 wt% isoquinoline (relative to the total reactant amount) was added dropwise to the reaction system, the temperature of the reaction solution was raised to 120 °C, and the reaction was carried out for 10 h. The reaction temperature was further increased to 190 °C, and the reaction was carried out for 24 h to obtain a viscous polyimide reaction solution. After cooling to room temperature, tannic acid was added to the system at a mass fraction of 10 wt% (relative to the total polyimide resin amount), and the mixture was stirred evenly. The synthesized adhesive was used to bond polyimide films, copper sheets, and glass plates. The solvent was removed at 80°C, and then the adhesive was cured at room temperature for 5 hours.

[0033] Comparative Example 2 Under nitrogen protection, BTDA monomer was dissolved in DMAc solvent. After complete dissolution, equimolar amounts of 1,3-bis(aminopropyl)tetramethyldisiloxane and 3,5'-diaminobenzoic acid were added to the dianhydride solution, wherein the molar fraction of 1,3-bis((aminopropyl)tetramethyldisiloxane) in the diamine was 30 mol%, the reactant mass fraction was controlled at 20 wt%, and the solvent mass fraction was 80 wt%. The mixture was stirred at room temperature for 18 h. Subsequently, 0.5 wt% of isoquinoline (relative to...) was added dropwise to the reaction system. (Total reactants), the reaction solution temperature was raised to 120℃ and reacted for 10 h. The reaction temperature was then further increased to 190℃ and reacted for 24 h to obtain a viscous polyimide reaction solution. After cooling to room temperature, 0.1 wt% NaOH and epichlorohydrin were added to the reaction system, wherein the molar fraction of epichlorohydrin was 30 mol% of the polyimide backbone. The reaction was carried out at 90℃ for 2 h. The synthesized adhesive was used to adhere polyimide films, copper sheets, and glass plates. The solvent was removed at 80℃, followed by curing at room temperature for 5 h.

[0034] Comparative Example 3 Under nitrogen protection, BTDA monomer was dissolved in DMAc solvent. After complete dissolution, an equimolar amount of 3,5'-diaminobenzoic acid was added to the dianhydride solution, controlling the reactant mass fraction to 20 wt% and the solvent mass fraction to 80 wt%. The mixture was stirred at room temperature for 18 h. Then, 0.5 wt% isoquinoline (relative to the total reactant amount) was added dropwise to the reaction system, and the reaction temperature was raised to 120 °C. The reaction was carried out for 10 h, and then the reaction temperature was further increased to 190 °C and carried out for 24 h, yielding a viscous polyimide reaction solution. After cooling to room temperature, 0.1 wt% NaOH and epichlorohydrin were added to the reaction system, wherein the molar fraction of epichlorohydrin was 30 mol% of the polyimide backbone. The reaction was carried out at 90 °C for 2 h. After cooling to room temperature, tannic acid was added to the system at a mass fraction of 10 wt% (relative to the total polyimide resin amount), and the mixture was stirred evenly. The synthesized adhesive was used to bond polyimide films, copper sheets, and glass plates. The solvent was removed at 80°C, and then the adhesive was cured at room temperature for 5 hours.

[0035] Performance testing: The adhesives prepared in Examples 1-5 and Comparative Examples 1-3 were tested for bonding performance after curing at room temperature. The results are shown in Table 1.

[0036] The adhesive bonding performance was tested using an lap shear test (GB / T 33334-2016), with a tensile rate of 50 mm·min. -1 .

[0037] Table 1

[0038] Analysis of the data in Table 1 shows that the high-temperature resistant adhesives prepared in Examples 1-5, containing siloxane units, epoxy side groups, and tannic acid components, exhibit high shear strength for PI films, copper sheets, and glass plates, and no interface damage occurs.

[0039] Compared with Example 1, Comparative Example 1 did not introduce epoxy units, so the bonding strength with the film, copper plate and glass plate was low, and there was a problem of interface damage. In Comparative Example 2, because tannic acid was not introduced, a rich hydrogen bond network was not formed between the molecular chains, and the bonding performance was also poor. In Comparative Example 3, siloxane units were not introduced. This type of high temperature resistant adhesive has poor adhesion to glass materials, and the adhesion decreased most significantly after high temperature treatment.

[0040] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A polyimide resin, characterized in that, Its main chain contains repeating imide rings and siloxane segments, and its side chains contain epoxy groups; The molar fraction of siloxane unit segments in the polymer resin backbone is (10-50) mol%. The molar fraction of epoxy side group segments is (30-50) mol%.

2. The method for preparing the polyimide resin according to claim 1, characterized in that, Polyimide resin is produced by condensation reaction of dianhydride monomer, diamine monomer containing carboxyl or hydroxyl groups and diaminosiloxane, followed by grafting reaction of epichlorohydrin with hydroxyl or carboxyl groups in the resin. The dianhydride monomer is selected from one or more combinations of 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, hexafluoro dianhydride, and bisphenol A type diether dianhydride; The diamine monomer containing a carboxyl or hydroxyl group is selected from one or more combinations of 3,5'-diaminobenzoic acid, 4,4'-diaminobiphenyl-2,2'-dicarboxylic acid, 9,9-bis(3-amino-4-hydroxyphenyl)fluorene, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane or 3,3'-dihydroxybenzidine; The diaminosiloxane is selected from one or more combinations of 1,3-bis(aminopropyl)tetramethyldisiloxane and diaminopropylpolydimethylsiloxane.

3. The preparation method according to claim 2, characterized in that, The preparation methods specifically include: S1. Under gas protection, the dianhydride monomer is dissolved in an organic solvent; S2. Under gas protection, diamines containing siloxane units and diamine monomers containing carboxyl or hydroxyl groups are gradually added to the dianhydride solution. After all the diamine monomers are dissolved, the mixture is stirred at room temperature for (18-24) h to obtain a polymer solution. S3. Add a catalyst to the polymer solution and heat the reaction solution to (100-120)℃. React at this temperature for (10-12)h. Further heat the reaction system to (190-200)℃ and react at this temperature for (12-24)h to finally obtain a viscous polyimide solution. S4. Add sodium hydroxide to the above-mentioned synthetic solution, add epichlorohydrin dropwise, and react at 90-100℃ for 2 hours.

4. The preparation method according to claim 3, characterized in that, The organic solvent in step S1 is selected from any one or a combination of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone; And / or, the gas mentioned in steps S1 and S2 is an inert gas or nitrogen; And / or, the total mass fraction of the solid reactants in step S2 is (15-25) wt%. And / or, in step S3, the molar ratio of the diamine containing a siloxane unit to the diamine containing a carboxyl or hydroxyl group is 1 / 9 to 5 / 5; And / or, the catalyst in step S3 is selected from pyridine or isoquinoline; And / or, in step S4, the amount of sodium hydroxide used is (0.1-0.2) wt% of the mass of epichlorohydrin.

5. A composition, characterized in that, The composition comprises the polyimide resin as described in claim 1 and tannic acid.

6. The composition according to claim 5, characterized in that, The mass of tannic acid in the composition is (10-20) wt% of the mass of the polyimide resin.

7. A method for preparing the composition according to any one of claims 5-6, comprising: Tannic acid was added to the polyimide resin solution for physical blending.

8. The method for preparing the composition according to claim 7, characterized in that, Tannic acid is added to the polyimide resin solution for physical blending under inert gas or nitrogen protection. And / or, add tannic acid to the polyimide resin solution and blend for 12-48 hours; And / or, add tannic acid to the polyimide resin solution for blending and then degas the mixture.

9. An application characterized in that, Use of the composition according to any one of claims 5-6 as a high-temperature resistant adhesive.

10. An application characterized in that, Use of the composition according to any one of claims 5-6 for bonding at the interface of the same or different materials, wherein the materials include: polymer film materials, metallic materials or inorganic non-metallic materials.

Citation Information

Patent Citations

  • A polyimide adhesive and its preparation method

    CN108641665B

  • High-temperature-resistant polyimide structure cementing agent and application thereof

    CN114395364A

Cited By

  • High-temperature-resistant adhesive and preparation method thereof

    CN121086751A

  • High-thermal-conductivity low-water-absorption epoxy molding sealing material for semiconductors

    CN122080590A